A multi-parameter study of groundwater–seawater interactions along Partido de La Costa, Buenos Aires Province, Argentina - Carretero, Silvina Claudia (2019)
Submarine groundwater discharge (SGD) is a complex hydrological process which occurs at the continent–ocean interface and plays an important role in coastal dynamics. The main objective of this study was to detect groundwater discharge from the sandy freshwater aquifer towards the Atlantic Ocean along the western coast of Buenos Aires Province (Argentina) using multiple methods. ²²²Rn as a tracer, electrical resistivity tomography (ERT), and hydrogeological information were applied to detect and quantify SGD. ²²²Rn activity was measured in wells, at the beach (tidal pools and surf zone) and along a transect ~ 200 m from the coastline coincident with geoelectrical measurements. Groundwater depth was measured in wells, and from these data, groundwater contour maps were made. ²²²Rn activity in wells varies from 16 and 173 dpm/L; at the beach, the values are between 28 and 48 dpm/L; and along the coastline, they oscillate between 1.3 and 20.5 dpm/L. The ERT shows a high resistivity layer close to 3–4 m depth from the sea floor indicating the presence of freshwater. Groundwater contour maps show discharge toward the continental plain to the west and toward the sea to the east. There is no precedent related to the application of these methodologies in the study area which results of interest for the knowledge of the coastal hydrodynamics.